2008
DOI: 10.1136/bjsm.2008.046151
|View full text |Cite
|
Sign up to set email alerts
|

Review on leptin and adiponectin responses and adaptations to acute and chronic exercise

Abstract: Leptin and adiponectin represent two newly discovered adipose tissue derived hormones; that are both associated with health status and glucose and free fatty acid (FFA) metabolism. Moreover, acute and chronic exercises affect body composition, carbohydrate and lipid metabolism. It is thus interesting to evaluate the effects of physical exercise and training on leptin and adiponectin levels. It seems that leptin concentration is not modified after short-term exercise (<60 min) or exercise that generates an ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
224
3
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(264 citation statements)
references
References 93 publications
(116 reference statements)
21
224
3
16
Order By: Relevance
“…Accordingly, it is reasonable to speculate that the reduction in body fat mass led to decreased expression of leptin and improvement in leptin resistance. Our results are in accordance with previous studies which showed that exercise programs resulting in reduced fat mass usually decreased leptin concentration (Bouassida et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, it is reasonable to speculate that the reduction in body fat mass led to decreased expression of leptin and improvement in leptin resistance. Our results are in accordance with previous studies which showed that exercise programs resulting in reduced fat mass usually decreased leptin concentration (Bouassida et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…One explanation for these findings is thought to be because of beneficial effects of physical activity (PA) on endothelial function and the relatively less well‐studied biomarkers of atherosclerosis 5, 6, 7, 8, 9, 10, 11, 12. The anti‐inflammatory effects of PA have been well documented with consistent findings of decreases in pro‐inflammatory markers C‐reactive protein (CRP) and interleukin‐6 (IL‐6) following brief exercise interventions,8, 9 in addition to decreases in leptin and increases in adiponectin levels with exercise‐induced fat loss 5. PA also improves endothelial function in terms of its ability to release the protein tissue‐plasminogen activator (t‐PA), but the influence of PA on the cell adhesion molecule E‐selectin is uncertain 6.…”
Section: Introductionmentioning
confidence: 99%
“…Bouassida et al (20) argued that leptin reduction occurs after the physical activities in which the energy consumption is higher than 800 kcal. Therefore, the higher energy consumption during intermittent exercise might be one possible cause of leptin reduction; as such reduction did not occur after the continuous exercise in this study.…”
Section: Discussionmentioning
confidence: 99%